Analisis Perancangan Sistem Informasi Medical Record Pada Poli Klinik Patologi Anatomi - Andriyas Hariyandi (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2020)
This is System very complex because have to earn to do record keeping of transaction start from inspection of laboratory, inspection of doctor, lodging, and apotek of Poli Clinic for the drug of road street, and also facility additional facility like infus, operation and others. For the system of inspection of just doctor, this system of this system have to earn to give information about ill history of patient, allergic of drug which in distress, drug history which have been consumed, doctor which have handled and inspection priode which have been done. For the inspection of, laboratory have to can give information about inspection type, laboratotium have to can give information about done inspection type and its result, what its of him which in giving by laboratory doctor about result of that inspection. Pathology Anatomy is science area doing pandemic research. Which in patient distress pursuant to anatomy which have been lifted from patient body checked by in anatomy pathology laboratory to know disease type.